Previous COVID-19 Infection and Antibody Levels After Vaccination - Ali, Hamad; Alahmad, Barrak; Al-Shammari, Abdullah A.; Alterki, Abdulmohsen; Hammad, Maha; Cherian, Preethi; Alkhairi, Irina; Sindhu, Sardar; Thanaraj, Thangavel Alphonse; Mohammad, Anwar; Alghanim, Ghazi; Deverajan, Sriraman; et al. (Frontiers in Public Health, 2021)
Background: The emergence of new COVID-19 variants of concern coupled with a global inequity in vaccine access and distribution has prompted many public health authorities to circumvent the vaccine shortages by altering vaccination protocols and prioritizing persons at high risk. Individuals with previous COVID-19 infection may not have been prioritized due to existing humoral immunity. Objective: We aimed to study the association between previous COVID-19 infection and antibody levels after COVID-19 vaccination. Methods: A serological analysis to measure SARS-CoV-2 immunoglobulin (Ig)G, IgA, and neutralizing antibodies was performed on individuals who received one or two doses of either BNT162b2 or ChAdOx1 vaccines in Kuwait. Generalized linear regression models adjusted for individual characteristics and comorbidities were fitted to compare the average levels of IgG and neutralizing antibodies between vaccinated individuals with and without previous COVID-19 infection. Results: A total of 1025 individuals were recruited. The mean levels of IgG, IgA, and neutralizing antibodies were higher in vaccinated subjects with previous COVID-19 infections than in those without. Regression analysis showed a steeper slope of decline for IgG in vaccinated individuals without than in those with previous COVID-19 infections. Conclusion: Previous COVID-19 infection appeared to elicit robust and sustained levels of SARS-CoV-2 antibodies in vaccinated individuals. Given the inconsistent supply of COVID-19 vaccines in many countries due to inequities in global distribution, our results suggest that even greater efforts should be made to vaccinate more people, especially individuals without previous COVID-19 infection.